2011
DOI: 10.1007/s00402-011-1285-6
|View full text |Cite
|
Sign up to set email alerts
|

The laser-pointer assisted angle reproduction test for evaluation of proprioceptive shoulder function in patients with instability

Abstract: The new LP-ART presented here is a technically simple, yet effective instrument for evaluation of the proprioceptive function of the shoulder. In contrast to former test setups it is feasible in daily routine. Compared to healthy controls, patients with unstable shoulder joints show significant proprioceptive disorders that can be quantified by the LP-ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 29 publications
5
32
0
2
Order By: Relevance
“…Although some researchers have speculated that individuals might have better joint position reproduction with the dominant limb as a result of training, others believed that the dominant limb might be less sensitive to joint position change because overuse of limbs could lead to cumulative micro injuries (Lephart, 1994;Balke, 2011). Studies by Balke et al (2011), Herrington et al (2010, and by Lephart et al (1994) demonstrated similar results that dominant and non-dominant shoulders did not differ in glenohumeral JPS. Previous research showed that fatigued shoulder muscles compromised the scapular and shoulder JPS performance in young healthy adults (Lee, 2003;Guo, 2011).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Although some researchers have speculated that individuals might have better joint position reproduction with the dominant limb as a result of training, others believed that the dominant limb might be less sensitive to joint position change because overuse of limbs could lead to cumulative micro injuries (Lephart, 1994;Balke, 2011). Studies by Balke et al (2011), Herrington et al (2010, and by Lephart et al (1994) demonstrated similar results that dominant and non-dominant shoulders did not differ in glenohumeral JPS. Previous research showed that fatigued shoulder muscles compromised the scapular and shoulder JPS performance in young healthy adults (Lee, 2003;Guo, 2011).…”
Section: Discussionsupporting
confidence: 55%
“…Various studies have measured shoulder JPS and showed its deficits in individuals with shoulder injury (Lephart, 1994;Dover, 2003;Lee, 2003;Tripp, 2006;Suprak, 2007;Herrington, 2010;Yang, 2010;Balke, 2011;Guo, 2011;Lin, Hung, & Yang, 2011). There have been only a few investigations into the scapular JPS despite its importance in the functioning of the shoulder complex.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Such a mechanism plays a substantive role in maintaining shoulder stability. 10,15,18,23 It has been shown that disruption of the shoulder capsuloligamentous complex after traumatic dislocation has a detrimental effect on proprioception, 4,22 which may recover after surgical restoration of the normal GHJ capsular tensioning. 25,29 Whereas open shoulder stabilization has been traditionally performed for this purpose, arthroscopic techniques for capsulolabral reconstruction gained popularity during the past decade with comparable clinical outcomes.…”
mentioning
confidence: 99%
“…Clinical assessment comprised the Quick-DASH work and sports module [20] and Walch-Duplay score. Last (2-year) follow-up included Rowe score [21], Simple Shoulder Test (SST) [22] and the "3S" satisfaction score after stabilization [23]; shoulder proprioception was assessed as the ability to reproduce a posture using a laser pointer on a wall-mounted target [24] (Fig. 5) and the Shoulder HyperAbduction Radiological Test (SHART) [25] ( Fig.…”
Section: Methodsmentioning
confidence: 99%